2016
DOI: 10.5301/hipint.5000409
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approach in Total HIP Arthroplasty: Supercapsular Percutaneously-Assisted

Abstract: The new generation of hip approaches have a strong anatomical basis, hip capsule preservation is a revolutionary concept, it ensures anatomical restoration, length and offset near to native joint. The Superpath® potentially minimises morbidity, reducing transfusion rates, allowing rapid recovery, shortening hospital stay and could save a significant cost to the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Artificial total hip arthroplasty (THA) is applied since the 1920s. THA can improve pain, motor function of the hip joint, quality of life of the patient, and correct deformities [ 9 ]. According to a systematic review and meta-analysis, the survival at 15 years of THA is estimated with almost 90% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial total hip arthroplasty (THA) is applied since the 1920s. THA can improve pain, motor function of the hip joint, quality of life of the patient, and correct deformities [ 9 ]. According to a systematic review and meta-analysis, the survival at 15 years of THA is estimated with almost 90% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a smaller series of the first 21 patients, the average operating time was 102.85 min (range 80–130 min). The mean acetabular inclination was 44.05° (26–60°) [2].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that there was no signi cant difference between both. Cardenas-Nylander C et al [29] showed that the average length of stay undergoing SuperPATH technology was 1.4 days, less than that of the conventional THA. Gofton W et al [30] conducted a study of 30-day readmission rates for 479 patients who performed THA.…”
Section: Discussionmentioning
confidence: 98%